Contesting the Boundaries of Sharia Compliance: Legalizing Income Smoothing in Indonesian Islamic Banking - Fakhrina, Agus; Arwani, Agus; Hamid, Abdul; Adeel, Nazia (UIN Sunan Kalijaga, 2025)
Economic pressures have prompted Islamic banks to implement income smoothing techniques when distributing returns on third-party funds, raising questions about the legitimacy of these practices from an Islamic legal perspective. This paper aims to examine the income smoothing guidelines issued by the National Sharia Council of the Indonesian Ulema Council and their impact on the distribution of third-party fund returns by Islamic banks. The primary data source for this research is a fatwa from the National Sharia Council, accessible on its official website. Employing Islamic legal discourse, this study finds that the income smoothing method for distributing third-party fund returns is approved by the National Sharia Council as a form of ḥīlah (a legal stratagem used to provide solutions and alleviate difficulties) to regulate profit recognition and reporting. This approval is grounded in istiḥsān (legal preference), which considers customary law (al-‘urf) and public interest (maṣlaḥah) as key justifications. Practically, this approval enables Islamic banks to remain competitive with conventional banks while also raising public awareness that there is little difference between Islamic and conventional banking.